2015
DOI: 10.1002/joc.4347
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal prediction of East Asian monsoon precipitation: skill sensitivity to various climate variabilities

Abstract: The sensitivity of the East Asian Monsoon (EAM) precipitation prediction skill to the variabilities of the tropical Indian and Pacific sea surface temperature (SST), the North Atlantic Oscillation (NAO), and the heating and snow cover over the Tibetan Plateau is evaluated in the framework of a linear Markov model. It is found that the tropical Indo‐Pacific SST helps to improve the prediction of EAM precipitation over oceanic regions and some localized areas over land, while the Indian Ocean alone does not show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…This is especially relevant here since the predictability of the EASM, and corresponding droughts or flooding, can be improved by accounting for the NAO influence (e.g., Wu et al 2009Wu et al , 2016b. This paper aims to address the shortfalls outlined above.…”
mentioning
confidence: 99%
“…This is especially relevant here since the predictability of the EASM, and corresponding droughts or flooding, can be improved by accounting for the NAO influence (e.g., Wu et al 2009Wu et al , 2016b. This paper aims to address the shortfalls outlined above.…”
mentioning
confidence: 99%
“…In the precipitation forecasting model, the statistical method and the climate model are widely employed (Shao et al 2017;Wu et al 2018;Mafi Gholami & Baharlouii 2019). When using the statistical method, Wu et al (2015) decomposed a variety of predictive variables by MEOF, and the Markov prediction model was constructed by using spatial models and the corresponding time coefficient. It was found that the model had good prediction skills for precipitation in Northeast Asia.…”
Section: Introductionmentioning
confidence: 99%
“…Summer precipitation in China has a close relation to the thermal effect of TP in spring (Yuan et al ., 2020). The sensible heat over TP was used as a factor to predict Eastern Asian monsoon precipitation (Wu et al ., 2015b). The surface sensible heat over TP in spring can indicate the occurrence of drought and flood downstream of the YZRB (Bai and Xu, 1999; Bai et al ., 2003).…”
Section: Introductionmentioning
confidence: 99%